INTERKONEKSI APLIKASI ADMINISTRASI PERKANTORAN DENGAN APLIKASI PELAYANAN PERIJINAN PEMERINTAH DAERAH - Fresiliasari, Oktavie; Suhardjo, Yohanes (Solusi, 2023)
This study aims to determine whether it is necessary to design and implement the interconnection of office administration applications (Srikandi) with licensing service applications (SiCantik Cloud). This research is classified as case study research which is qualitative research. Research data was collected using in-depth interviews, direct observation and documentation methods. To test the credibility of the data, a triangulation test was carried out. The results of this study indicate the need to design and implement the interconnection of the Srikandi application with the SiCantik Cloud application at the One-Stop Integrated Investment and Licensing Service, Sorong Regency.
Keywords: Interconnection; Srikandi; SiCantik Cloud.